Utilizing settling ponds in reclaimed mine sites in Indonesia: Linking georesources and fish culture - Mujahid, Muhammad; Adlan, Qi; Diatin, Iis; Hadiroseyani, Yani; Matangaran, Juang Rata (Brawijaya University, 2025)
Abandoned mine quarries are a growing concern in many developing countries, especially in the Indonesian archipelago, where challenging geography often hinders regulatory inspections. Repurposing quarry settling ponds for fish culture poses a challenge because, while these ponds offer an opportunity to convert post-mining geological assets into sustainable resources, not all fish species can survive the poor water conditions typical of these ponds. Reclaiming post-mining land offers an opportunity to convert these geological sites into productive fish culture areas. In this study, a settling pond at a post-mining site in Sukabumi, West Java, Indonesia, was treated, and fish species were selected using a Multi-Criteria Decision-Making method to ensure survivability and economic sustainability. The three best species were tested in a 1.5 m x 1 m x 1 m floating net cage with 200 fish stocked per cage, with a culture time of 70 days. The selected fish species cultured were catfish (Clarias gariepinus), common carp (Cyprinus carpio), and tilapia (Oreochromis niloticus). Survival rates ranged from 53.5 to 86%, showing the pond’s potential for fish farming. Catfish and tilapia exhibited the highest growth, survival, and production rates, more than twice that of common carp, highlighting their suitability for sustainable fish culture in reclaimed settling ponds.